An efficient subset selection method for supplier selection under multiple quality characteristics. Issue 2 (4th March 2019) - Lan, Yu-jie; Lin, Chen-ju
Abstract: Supplier selection is a strategic decision for production management. Evaluating the performance of suppliers and selecting the one with the highest quality are important tasks. An electronic component is required to meet specifications in practical applications. Generally, the supplier selection procedure must evaluate the overall yield with respect to multiple quality characteristics. A subset selection method is proposed to identify the supplier with the highest overall yield under multiple quality characteristics. The confidence interval of each difference from the unknown best supplier is provided in terms of the overall yield index. In the demonstration, the subset selection method effectively selected the best pre-amplifier supplier for a manufacturer producing microelectromechanical systems (MEMS) sensors. Pre-amplifier gain, absolute reference voltage and module quiescent current were simultaneously evaluated for supplier selection.